2020
DOI: 10.1038/s42005-020-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optical beam steering and tuning system based on electrowetting driven fluidic rotor

Abstract: Reconfigurable beam steering components are indispensable to support optical and photonic network systems operating with high adaptability and with various functions. Currently, almost all such components are made of solid parts whose structures are rigid, and hence their functions are difficult to be reconfigured. Also, optical concentration beam steering is still a very challenging problem compared to radio frequency/microwave steering. Here we show a watermill-like beam steering system that can adaptively g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The operation of the EWOD device relies on the application of the electric potential to change the wetting properties of the hydrophobic layer, resulting in a change in the contact angle and therefore actuating the droplet. Fluoropolymers such as Cytop are the most commonly used hydrophobic material for developing EWOD devices for both open and closed configurations [ 87 ]. In addition, other polymers, such as Teflon and Pluronics, have been explored due to their excellent hydrophobic properties by simply spin-coating a layer of a few nanometres thick [ 87 ].…”
Section: Ewod: Working Principle and Design Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation of the EWOD device relies on the application of the electric potential to change the wetting properties of the hydrophobic layer, resulting in a change in the contact angle and therefore actuating the droplet. Fluoropolymers such as Cytop are the most commonly used hydrophobic material for developing EWOD devices for both open and closed configurations [ 87 ]. In addition, other polymers, such as Teflon and Pluronics, have been explored due to their excellent hydrophobic properties by simply spin-coating a layer of a few nanometres thick [ 87 ].…”
Section: Ewod: Working Principle and Design Parametersmentioning
confidence: 99%
“…Fluoropolymers such as Cytop are the most commonly used hydrophobic material for developing EWOD devices for both open and closed configurations [ 87 ]. In addition, other polymers, such as Teflon and Pluronics, have been explored due to their excellent hydrophobic properties by simply spin-coating a layer of a few nanometres thick [ 87 ]. Various studies have demonstrated that the surface roughness of the hydrophobic layer is crucial for determining the actuation voltage [ 55 ].…”
Section: Ewod: Working Principle and Design Parametersmentioning
confidence: 99%
“…Electrowetting is used in several applications, such as micro-drop generation, mixing and splitting [ 1 , 2 ], high-speed droplet actuation [ 3 , 4 ], chip cooling [ 5 ], drug release and clinical diagnosis [ 6 , 7 ], e-paper and electronic display [ 8 , 9 ], energy harvesting [ 10 ], solar indoor lighting [ 11 ], optics and beam steering [ 12 , 13 ]. In most electrowetting studies, the primary focus has been to observe the drop deformation and contact-angle change when the applied voltage is varied.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the prescribed transport of the sample droplet towards the specific sensing spot before its complete evaporation is the prerequisite for the accurate screening of targeted analytes. During the past two decades, especially inspired by droplet motion on spider silk [11], cactus spines [12], and Cotula fallax plant [13], the directional transport of droplet has been realized through various strategies: (1) wettability gradient induced by surface textures [14], chemical functionalizations [15], thermal gradient [16] or electrowetting effect [17,18]; (2) external body forces including gravity [19], magnetic force [20] and electric force [21]; and (3) Laplace pressure difference due to the confinement in asymmetric geometries [11,[22][23][24][25][26][27][28]. However, the complex geometric structures, extra force/temperature/concentration fields, and functionalized surfaces with fragile micro/nanostructures involved in these technologies still restrict their practical applications.…”
Section: Introductionmentioning
confidence: 99%